Studies on musical diversity : methodological approaches - Jahnichen, Gisa (Universiti Putra Malaysia Press, 2011)
Gisa Jahnichen’s book Studies on Musical Diversity – Methodological Approaches consists of twelve studies on musical diversity in the broadest sense in which a variety of methods depending on the particular research topic, the main research questions and the dimension of expected response are applied. It is segmented into six chapters, each with a pair of studies that can be compared in methodology, research aim and prospective function. Their vision under different headlines emphasizes the main focus given although each study comprises a set of different methods and includes varying formats of presentation. All twelve studies are revised and extended parts of researches undertaken in a time frame of about fifteen years. They were conducted to be applied in further research and in music practice, to enrich the scientific horizon of young scholars and colleagues and to provoke further discussions. Their aim is to contribute to an academic tradition that places knowledge processing and distribution into the centre of research.